Pregnancy and COVID‐19: pharmacologic considerations. (1st February 2021) - D'Souza, R.; Ashraf, R.; Rowe, H.; Zipursky, J.; Clarfield, L.; Maxwell, C.; Arzola, C.; Lapinsky, S.; Paquette, K.; Murthy, S.; Cheng, M. P.; Malhamé, I.
ABSTRACT: In this review, we summarize evidence regarding the use of routine and investigational pharmacologic interventions for pregnant and lactating patients with coronavirus disease 2019 (COVID‐19). Antenatal corticosteroids may be used routinely for fetal lung maturation between 24 and 34 weeks' gestation, but decisions in those with critical illness and those < 24 or > 34 weeks' gestation should be made on a case‐by‐case basis. Magnesium sulfate may be used for seizure prophylaxis and fetal neuroprotection, albeit cautiously in those with hypoxia and renal compromise. There are no contraindications to using low‐dose aspirin to prevent placenta‐mediated pregnancy complications when indicated. An algorithm for thromboprophylaxis in pregnant patients with COVID‐19 is presented, which considers disease severity, timing of delivery in relation to disease onset, inpatient vs outpatient status, underlying comorbidities and contraindications to the use of anticoagulation. Nitrous oxide may be administered for labor analgesia while using appropriate personal protective equipment. Intravenous remifentanil patient‐controlled analgesia should be used with caution in patients with respiratory depression. Liberal use of neuraxial labor analgesia may reduce the need for emergency general anesthesia which results in aerosolization. Short courses of non‐steroidal anti‐inflammatory drugs can be administered for postpartum analgesia, but opioids should be used with caution due to the risk of respiratory depression. For mechanically ventilated pregnant patients, neuromuscular blockade should be used for the shortest duration possible and reversal agents should be available on hand if delivery is imminent. To date, dexamethasone is the only proven and recommended experimental treatment for pregnant patients with COVID‐19 who are mechanically ventilated or who require supplemental oxygen. Although hydroxycholoroquine, lopinavir/ritonavir and remdesivir may be used during pregnancy and lactation within the context of clinical trials, data from non‐pregnant populations have not shown benefit. The role of monoclonal antibodies (tocilizumab), immunomodulators (tacrolimus), interferon, inhaled nitric oxide and convalescent plasma in pregnancy and lactation needs further evaluation. © 2020 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.